2017
DOI: 10.1186/s13099-017-0215-8
|View full text |Cite|
|
Sign up to set email alerts
|

CRISPR-like sequences in Helicobacter pylori and application in genotyping

Abstract: BackgroundMany bacteria and archaea possess a defense system called clustered regularly interspaced short palindromic repeats (CRISPR) associated proteins (CRISPR-Cas system) against invaders such as phages or plasmids. This system has not been demonstrated in Helicobacter pylori. The numbers of spacer in CRISPR array differ among bacterial strains and can be used as a genetic marker for bacterial typing.ResultsA total of 36 H. pylori isolates were collected from patients in three hospitals located in the cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 45 publications
1
24
0
1
Order By: Relevance
“…This element also forms a secondary structure and can affect the toxicity of Listeria, which depends on the polynucleotide phosphorylase (PNPase) when acting. It has been reported that CRISPR like elements was found in the vlpC gene of Helicobacter pylori and can be used for virulence typing of Helicobacter pylori . Further research remains to be done whether these independent CRISPR elements of Staphylococcus have an effect on their virulence, or whether they have other undiscovered effects.…”
Section: Discussionmentioning
confidence: 99%
“…This element also forms a secondary structure and can affect the toxicity of Listeria, which depends on the polynucleotide phosphorylase (PNPase) when acting. It has been reported that CRISPR like elements was found in the vlpC gene of Helicobacter pylori and can be used for virulence typing of Helicobacter pylori . Further research remains to be done whether these independent CRISPR elements of Staphylococcus have an effect on their virulence, or whether they have other undiscovered effects.…”
Section: Discussionmentioning
confidence: 99%
“…In the original version of this article [ 1 ], published on 17 November 2017, Table 2 contains an error: the first “T” in the first sequence in the column ‘Consensus direct repeats (CDRs) sequences’ has been incorrectly underlined. In Table 2, the underlining indicates the Consensus sequence.…”
Section: Correction To: Gut Pathog (2017) 9:65 101186/s13099-017-021mentioning
confidence: 99%
“…CRISPRFinder revealed the existence of additional loci to the CRISPR-like locus inserted into the VlpC gene described by Bangpanwimon et al, 2017 15 (Fig. S2, S5, S7, and S9).…”
Section: Discussionmentioning
confidence: 70%
“…The lack of this system in some prokaryotes has been related to the increase in the capacity to integrate exogenous DNA in the genome of these bacteria and, resulting in the acquisition of new functions, which can confer an adaptive advantage to these strains, particularly during their transition to pathogenesis . But recently, Bangpanwimon et al, 2017 15 reported the presence of CRISPR-type sequences inserted into the VlpC gene of H pylori. In that study, the detection was performed by PCR in partial regions of the genome of Thailand isolates 15 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation